O(6)-methylguanine-DNA methyltransferase activity is associated with response to alkylating agent therapy and with MGMT promoter methylation in glioblastoma and anaplastic glioma - Bobola, Michael S. (BBA Clin, 2014)
BACKGROUND: CpG methylation in the O(6)-methylguanine-DNA methyltransferase (MGMT) promoter is associated with better outcome following alkylating agent chemotherapy in glioblastoma (GBM) and anaplastic glioma (AG). To what extent improved response reflects low or absent MGMT activity in glioma tissue has not been unequivocally assessed. This information is central to developing anti-resistance therapies. METHODS: We examined the relationship of MGMT activity in 91 GBMs and 84 AGs with progression-free survival (PFS) following alkylator therapy and with promoter methylation status determined by methylation-specific PCR (MSP). RESULTS: Cox regression analysis revealed that GBMs with high activity had a significantly greater risk for progression in dichotomous (P ≤ 0.001) and continuous (P ≤ 0.003) models, an association observed for different alkylator regimens, including concurrent chemo-radiation with temozolomide. Analysis of MGMT promoter methylation status in 47 of the GBMs revealed that methylated tumors had significantly lower activity (P ≤ 0.005) and longer PFS (P ≤ 0.036) compared to unmethylated tumors, despite overlapping activities. PFS was also significantly greater in methylated vs. unmethylated GBMs with comparable activity (P ≤ 0.005), and among unmethylated tumors with less than median activity (P ≤ 0.026), suggesting that mechanisms in addition to MGMT promote alkylator resistance. Similar associations of MGMT activity with PFS and promoter methylation status were observed for AGs. CONCLUSIONS: Our results provide strong support for the hypotheses that MGMT activity promotes alkylator resistance and reflects promoter methylation status in malignant gliomas. GENERAL SIGNIFICANCE: MGMT activity is an attractive target for anti-resistance therapy regardless of methylation status.